Strike while the iron is hot - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Strike while the iron is hot Metal working or blacksmithing is an ancient tradition in most parts of Africa, but traditionally the skills were jealously guarded and were often restricted to certain families. Now mechanization and other aspects of...